2018
DOI: 10.1038/s41598-018-23884-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex I activity signals antioxidant response through ERK5

Abstract: Oxidative phosphorylation (OXPHOS) generates ROS as a byproduct of mitochondrial complex I activity. ROS-detoxifying enzymes are made available through the activation of their antioxidant response elements (ARE) in their gene promoters. NRF2 binds to AREs and induces this anti-oxidant response. We show that cells from multiple origins performing OXPHOS induced NRF2 expression and its transcriptional activity. The NRF2 promoter contains MEF2 binding sites and the MAPK ERK5 induced MEF2-dependent NRF2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 53 publications
4
29
0
1
Order By: Relevance
“…DCA causes metabolic stress by inhibiting PDK1 in AML cells 33,34 . This forces cells to decrease glycolysis and increase oxidative phosphorylation (OXPHOS) 3335 .…”
Section: Resultsmentioning
confidence: 99%
“…DCA causes metabolic stress by inhibiting PDK1 in AML cells 33,34 . This forces cells to decrease glycolysis and increase oxidative phosphorylation (OXPHOS) 3335 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, various mitochondrial abnormalities can be signaled to the cytosol by non-ROS-related mechanisms, as seen in mitochondrial retrograde signaling, such as in the C. elegans ATFS-1 system, in which the drop in membrane potential inhibits peptide transport activity and proteolysis, leading to the nuclear translocation of ATFS-1 [34]. Regarding Nrf2, it has been reported that alterations in complex I activity may determine Nrf2 gene expression via the ERK5-myocyte enhancer factor 2 (MEF2) pathway in a ROS-independent manner [27,35]. However, several reports have shown that changes in mtROS generation through alterations of the level of SOD2 [36] or mitochondria-localized paraquat [37] actually change the cellular response, indicating that alterations in mtROS actually signals to the cytosol using unknown signaling mediators or cascades.…”
Section: Activation Of Nrf2 By Mtrosmentioning
confidence: 99%
“…mROS exposure induces the prompt activation of Nrf2 through degradation of its allosteric inhibitor, kelch-like ECH-associated protein 1 (KEAP1). Although Nrf2 was originally deemed a tumour suppressor, recent findings have revealed its protumoral function that not only confers oxidative stress resistance but also controls ROS production via NADPH oxidase [20] and directly activates cancer-associated metabolic pathways [21] , [22] , [23] . Therefore, constitutive stabilization and activation of Nrf2 have been associated with poor prognosis in several types of cancer [24] .…”
Section: Mitochondria-dependent Regulation Of Malignant Energetic Stamentioning
confidence: 99%